Makna Pembinaan Rohani bagi Guru dan Karyawan di Sekolah Kristen: Kajian Fenomenologis tentang Spiritualitas dan Kepuasan Kerja - Martinus Tjahjadi; Christiansen Gabriel; Heryanto Panjaitan; Maria Donata Dona Kwartantri; Corry Limmelda (Jurnal Ketopong Pendidikan, 2025)
Within Christian educational settings, spiritual formation plays an important role in shaping how employees experience meaning, resilience, and well-being at work. This qualitative phenomenological study explores the lived experiences of teachers and staff regarding spiritual formation in a Christian school and how these experiences shape work meaning and job satisfaction. Data were collected through in-depth interviews with five participants and analysed using phenomenological interpretation. The findings reveal that spiritual formation transforms work into a meaningful calling, strengthens resilience in facing professional challenges, fosters supportive communal relationships, and contributes to job satisfaction beyond material rewards. The study concludes that spiritual formation functions as a foundational experiential process that integrates spirituality, resilience, and job satisfaction within the context of Christian education.